1986
DOI: 10.1159/000298952
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine-Binding Globulin in Spontaneous Abortion

Abstract: Thyroxine-binding globulin (TBG), thyroxine-binding prealbumin (TBPA), thy-roxine (T4), free T4, triiodothyronine (T3) and thyroid-stimulating hormone (TSH) were studied in 144 apparently healthy, euthyroid pregnant women displaying miscarriages. In an additional group of 18 aborting women a frozen blood sample drawn in early pregnancy was similarly analyzed for the thyroid components as well as for human chorionic gonadotropin (HCG). The values were compared to those of normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…[8] During preeclampsia, involvement of liver and kidney may lead on to decreased peripheral conversion of T 4 to T 3 ; hence, decreasing T 3 levels. [9] Also, “low T 3 syndrome” has been reported in preeclampsia. [10] Loss of proteins and protein-bound hormones in the urine of preeclamptics may also contribute to low TT 3 levels.…”
Section: Discussionmentioning
confidence: 99%
“…[8] During preeclampsia, involvement of liver and kidney may lead on to decreased peripheral conversion of T 4 to T 3 ; hence, decreasing T 3 levels. [9] Also, “low T 3 syndrome” has been reported in preeclampsia. [10] Loss of proteins and protein-bound hormones in the urine of preeclamptics may also contribute to low TT 3 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The infant birth weight was found to be related to the maternal serum albumin level in situa tions where there was heavy proteinuria such as the nephrotic syndrome [10], In normal pregnancy, the increasing production of pla cental estrogen during pregnancy stimulates the hepatic synthesis of TBG [11][12][13][14][15], and this is reflected by a decrease in T3U [16]. As TBG concentration is reported to be lower in unsuccessful pregnancies [17], this decrease may be a useful indicator of placental function deteriora tion in pregnancy [5], We think that the placental dys function may cause failure in estrogen production, there fore decrease in TBG, TT3 and TT4 and simultaneously growth failure to the fetus. We found a significant correla tion between birth weight and maternal TBG levels which was similar to that of Lao et al [5].…”
Section: Bw -Ft 4imentioning
confidence: 99%
“…Both TBG and T3U reflect the plasma concentration of thyroid-hormone-binding protein, and in normal pregnancy, TBG concentration increases and this is reflected by a decrease in T3U, due to the effect of increased circulating oestrogen concentration [7], Our findings may therefore reflect the circulating oestrogen level, which has been shown to be low in association with pre-eclampsia and fetal growth retardation [8]. As TBG concentration is reported to be lower in unsuccessful pregnancies [5], a decreased TBG concentration may be a useful indicator of deterioration of placental function in pregnancy.…”
Section: Discussionmentioning
confidence: 66%
“…Changes in thyroxine-binding globulin (TBG) in particular merits further examination. A relationship between a low TBG level and habitual abortion has been reported [3,4], In a recent study [5], significantly lower values of TBG were found in women with spontaneous abortion. Thus, the measurement of TBG may be useful in the assessment of pre-eclamptic pregnancies.…”
Section: Introductionmentioning
confidence: 84%